Experimental investigations of the effect of the neutral gas pressure on the separate control of ion energy and flux in dual frequency capacitively coupled plasmas - Saikia, Partha; Bhuyan, Heman; Yap, Seong Ling; Escalona, Miguel; Favre, Mario; Wyndham, Edmund; Schulze, Julian (AIP Publishing, 2019)
Classical dual-frequency capacitively coupled plasmas (2f CCPs) operating at low pressures and significantly different frequencies are often used for a variety of applications in semiconductor manufacturing in order to control the mean ion energy at the electrodes separately from the ion flux. However, recent computational studies have indicated that this separate control is limited by the frequency coupling effects and by the contribution of secondary electrons to the ionization dynamics [Donkó et al., Appl. Phys. Lett. 97, 081501 (2010); Schulze et al., Plasma Sources Sci. Technol. 20, 045007 (2011)]. Here, we verify these simulation results experimentally by measuring the ion flux to an electrode as a function of the low frequency (LF) and high frequency power at different neutral gas pressures in a 2f CCP operated at 2.26 MHz and 13.56 MHz in argon. In agreement with previous computational predictions, we find the ion flux to decrease as a function of the LF power at a low pressure of 1 mTorr due to the frequency coupling and to increase as a function of the LF power at a higher pressure of 60 mTorr due to the presence of secondary electrons. These experimental findings show that separate control of ion properties in classical 2f CCPs is generally not possible, but potentially limited to specific discharge conditions. © 2019 Author(s).